1998
DOI: 10.1101/gad.12.18.2842
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic inactivation of a human SWI/SNF chromatin remodeling complex

Abstract: During mitosis, chromatin is condensed into mitotic chromosomes and transcription is inhibited, processes that might be opposed by the chromatin remodeling activity of the SWI/SNF complexes. Brg1 and hBrm, which are components of human SWI/SNF (hSWI/SNF) complexes, were recently shown to be phosphorylated during mitosis. This suggested that phosphorylation might be used as a switch to modulate SWI/SNF activity. Using an epitope-tag strategy, we have purified hSWI/SNF complexes at different stages of the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
222
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(239 citation statements)
references
References 48 publications
15
222
0
2
Order By: Relevance
“…In fact, although cdk1 is the essential kinase for G2-M transition and phosphorylates a wide variety of proteins, neither cyclin A/cdk1 nor cyclin B/cdk1 complexes are able to phosphorylate SWI/ SNF subunits in vitro. Intriguingly, MEK1-activated ERK1 inhibits SWI/SNF activity by direct phosphorylation of BRG1, Brm, and BAF155, while PP2A phosphatase reactivates the chromatin remodeling function of the complex (Sif et al, 1998). This model supports the concept that the assembly of BRG1/Brm with BAF155 might form the specific substrate for cell cycle-regulated kinase cascade signaling to SWI/SNF to dictate the configuration of the chromatin.…”
Section: Phosphorylation-dependent Inactivation Of Swi/snf In Mitosissupporting
confidence: 64%
See 1 more Smart Citation
“…In fact, although cdk1 is the essential kinase for G2-M transition and phosphorylates a wide variety of proteins, neither cyclin A/cdk1 nor cyclin B/cdk1 complexes are able to phosphorylate SWI/ SNF subunits in vitro. Intriguingly, MEK1-activated ERK1 inhibits SWI/SNF activity by direct phosphorylation of BRG1, Brm, and BAF155, while PP2A phosphatase reactivates the chromatin remodeling function of the complex (Sif et al, 1998). This model supports the concept that the assembly of BRG1/Brm with BAF155 might form the specific substrate for cell cycle-regulated kinase cascade signaling to SWI/SNF to dictate the configuration of the chromatin.…”
Section: Phosphorylation-dependent Inactivation Of Swi/snf In Mitosissupporting
confidence: 64%
“…These molecular events result in the reversible inactivation of SWI/SNF activity and the displacement of the remodeling complexes from the condensed chromatin (Muchardt et al, 1996;Reyes et al, 1997;Sif et al, 1998). To date, it is not clear which kinases are responsible for the phosphorylation of SWI/SNF subunits in vivo, and which phosphatases are required for reactivating dephosphorylation at the beginning of the G1 phase of the cell cycle.…”
Section: Phosphorylation-dependent Inactivation Of Swi/snf In Mitosismentioning
confidence: 99%
“…Transfected cells were grown in the presence of 10 g͞ml puromycin, and individual colonies were isolated and analyzed for Flag-BRAF35 expression. A cell line expressing Flag-tagged BRAF35, FBRAF35-4, were used for the affinity purification of Flag-BHC as described previously for the Flag-Ini 1-11 cell line (10,28).…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of some remodeling proteins causes lethality indicating that these ATPases perform essential functions that cannot be replaced by other remodeling proteins. Furthermore, distinct remodeling complexes target different cellular genes and their remodeling activities as well as expression can be differentially regulated during cell cycle and differentiation Sif et al, 1998;Schultz et al, 2001;Kadam and Emerson, 2003;Johnson et al, 2004;Reisman et al, 2005). In this review, we will highlight the functions of major chromatin remodeling complexes.…”
Section: Atp-dependent Chromatin Remodelersmentioning
confidence: 99%
“…During mitosis, phosphorylation of BRM leads to its degradation while BRG1 phosphorylation renders it inactive (Sif et al, 1998). Biochemical characterization of BRG1 and BRM-based SWI/SNF complexes showed that both complexes are distinct, and that BRG1-based SWI/SNF complex can be fractionated into two separate complexes (BRG1 complex I and II), which differ by the presence of mSIN3/HDAC and PRMT5 corepressor proteins in BRG1 complex I (Sif et al, 1998(Sif et al, , 2001Pal et al, 2003). Chromatin remodeling assays showed that both forms of BRG1 complex and the BRM complex remodel nucleosomes differently in vitro (Sif et al, 2001).…”
Section: Swi2/snf2-related Chromatin Remodeling Complexesmentioning
confidence: 99%